Should Sri Lanka attempt to achieve self-sufficiency in pulses? - Natarajan, Kiruthika; Thibbotuwawa, Manoj; Babu, Suresh Chandra (International Food Policy Research Institute, 2024)
Agriculture is the mainstay of Sri Lanka’s rural economy and employs about 26.5 percent of the country’s total employed population, rural and urban (Department of Census and Statistics [DCS] 2023a). Paddy occupies the largest portion of cropland; tea, rubber, coconut, spices, fruits, vegetables, pulses, and other cereals occupy the rest (Thibbotuwawa 2021; Senanayake and Premaratne 2016; Adhikari nayake 2005). Nonetheless, food and nutrition security remain a major challenge: nearly 3.9 million people, or 17 percent of Sri Lankans, experience moderately acute food insecurity; nearly 10,000 are severely acute food insecure; and 56 percent of households have adopted food-based coping strategies, including reducing meal portion sizes (36 percent) and skipping meals (19 percent) (FAO 2023a). Moreover, the prevalence of underweight in women and anaemia in adolescent girls and women is high in South Asia (UNICEF 2023), and micronutrient (iron, zinc, and/or folate) deficiencies are also highest there (72 percent).